A Critique of the Interaction of Two Major Sects with Narrations of the Excellences of Suras (Chapters) Based on the Rule of Tolerance in the Evidence of Traditions - Sayyid Ali Delbari; Alborz Mohaqiq Garfami (آموزه‌های قرآنی)
One of the most frequent rules in various areas of demonstrative jurisprudence of Two Major Sects of Islam religion is a rule that is known among Shīʿa as “tolerance in the evidence of traditions” (Arabic: التسامح فی أدلّة السنن) and in Sunnī as “latitudinarianism in documents” (Arabic: التساهل فی أسانید). Believers in the general application of this rule have based it for reasons such as consensus (Arabic: إجماع), tradition famous through practice (Arabic: الشهرة العملیّة), and rational judgement (intellectual judgement) and a group of aḥādīth (Arabic: أحادیث, plural form for ḥadīth, literally “talk” or “discourse”) called “Akhbar-e- Man Balagh” (Arabic: أخبار من بلغ). The understanding of the aforementioned narrations and the extent of application of this rule has caused a conflict of opinions among scholars. The narrations containing the excellences of suras of the Holy Book of Quran is one of the fields of application of the rule of tolerance. The present research has explained the types of exposure to this group of narrations based on the rule of tolerance by using descriptive-exploratory method and using library sources and seeks to find a suitable approach about narrations of the excellences of suras (chapters) of the Holy Book of Quran. The interaction with these narrations is organized based on a special reading of the rule of tolerance in the selected approach, which is based on a rational interpretation of the contents of Man-Balagh (Arabic: من بلغ)’s narrations and is compatible with the indications of some verses and traditions. The use of weak narrations containing the excellences of suras (chapters) will be permissible based on this approach considering three conditions and without any certainty of attributing these narrations to Sharʿ (Islamic rules).